(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The food manufacturing industry is at the nexus of evolving consumer expectations, stringent regulatory requirements, and the need for operational efficiency. In this landscape, cloud-based quality control systems have emerged as a transformative force, offering innovative solutions to address the multifaceted challenges faced by the industry. This comprehensive review paper explores the integration of cloud computing technologies into quality control processes within the food manufacturing sector, providing a thorough analysis of the evolution, components, benefits, challenges, and strategies for successful implementation. The review begins by elucidating the significance of quality control in food manufacturing, emphasizing the role it plays in ensuring product safety, consistency, and integrity. It then introduces cloud computing and its relevance to quality control, setting the stage for a detailed examination of how cloud technology is reshaping the industry.